Pencegahan Stunting Lembang Rindingallo, Kecamatan Rindingallo, Kabupaten Toraja Utara - Anjelin Anjelin; Marson Palloan; Monika Monika; Rahma Gusmawati Tammu (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
This service is an academic activity that has a definite theme and program in a condition where the activity partners are aligned with the implementation of research programs and community service. From the data obtained by researchers, the research location really needs to improve nutrition because there are still many children affected by stunting and pregnant women who suffer from chronic energy deficiency (CED) and so the research location was chosen as a Stunting Prevention center for approximately 45 days. So that the community in Lembang and the community health center implement the Happy Kitchen to Prevent Stunting. This research aims to support the community to participate and involve active participation from the community, government, health institutions and related stakeholders to achieve maximum results in preventing stunting in Lembang Rindingallo. The research subjects are the people at the research location. Data collection techniques in this research are observation, interviews and documentation. The method used in this research is providing education, providing healthy food through the Dapur Bahagia Prevent Stunting program for children who fall into the stunting group and pregnant women with KEK. One of the work programs that we implement is Stunting Prevention. Through this work program, it is hoped that with the Happy Kitchen program to prevent stunting, the needs and health of children affected by stunting and pregnant women with KEK in Lembang Ridingallo can be prevented.